2D Magnetotelluric (MT) Modelling for Geothermal System Interpretation - Eko Minarto; Mohammad Istajarul Alim; Ahmad Zarkasy (Jurnal Fisika dan Aplikasinya, 2025)
Geothermal systems are areas beneath the earth’s surface that store circulating heat energy. The heat energy stored in the geothermal system can be utilized by humans as an environmentally friendly alternative energy. Determining the geothermal system area requires geophysical exploration methods that have deep enough penetration and can distinguish soil structures based on the value of resistivity. One method that is effective in determining geothermal systems is the magnetotelluric (MT) method. This method receives electric and magnetic field signals from the induction of subsurface rocks to the electromagnetic wave activity of solar storms and lightning. The signal is then processed to produce a resistivity value. This type of resistance data can then present the structure of the geothermal system, including impermeable rocks, reservoirs and magmatic intrusion zones. This study also collaborated with supporting geological and geochemical data. The results of the magnetotelluric method analysis for the geothermal system of this study area are suspected to have caps rocks with a resistivity of less than 10 m spread near the surface. Reservoirs that have a resistivity of 10-40 m are located at a depth of about 1000 m below the surface based on the interpretation of all data.